2012
DOI: 10.1590/s0100-29452012000300014
|View full text |Cite
|
Sign up to set email alerts
|

Registro da ocorrência de Meloidogyne incognita no porta-enxerto 'IAC 766-Campinas' no estado de Pernambuco e reação de porta-enxertos e de cultivares copa de videira a Meloidogyne spp.

Abstract: RESUMO -Relata-se a ocorrência de Meloidogyne incognita (Est. i2) em pomar de videira na cidade de Petrolina, Pernambuco. Plantas da cultivar Festival enxertadas sobre 'iAC 766-Campinas', atacadas por Meloidogyne incognita, apresentavam sintomas de menor vigor, folhas amarelecidas e folhagem mais esparsa, e raízes com numerosas galhas em meio ao cultivo de feijão-de-porco (Canavalia ensiformis), também atacado pelo nematoide. Com o objetivo de avaliar a resistência de quatro porta-enxertos tropicais, oito de c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…These results partially align with those of Gutiérrez-Gutiérrez et al 2011, a study that found 110R and SO4 rootstocks of the Cabernet Sauvignon variety to present low quantities of M. javanica and M. arenaria galls. Results similar to the present study were also obtained by Somavilla et al (2012), a study in which the Harmony, Kober 5BB, and SO4 rootstocks of Chardonnay had low quantities of M. incognita and M. arenaria galls.…”
Section: Discussionsupporting
confidence: 90%
“…These results partially align with those of Gutiérrez-Gutiérrez et al 2011, a study that found 110R and SO4 rootstocks of the Cabernet Sauvignon variety to present low quantities of M. javanica and M. arenaria galls. Results similar to the present study were also obtained by Somavilla et al (2012), a study in which the Harmony, Kober 5BB, and SO4 rootstocks of Chardonnay had low quantities of M. incognita and M. arenaria galls.…”
Section: Discussionsupporting
confidence: 90%
“…Quebranta and Torontel cultivars show a high susceptibility, with an RF = 2.97 and 2.28, respectively (Table 1). However, no other studies have indicated the susceptibility reaction of these cultivars, although similar behavior was evident to the cultivars evaluated by Somavilla et al (2012), Aballay and Vilches (2015).…”
Section: Resultsmentioning
confidence: 69%
“…Similarly, SO4 is resistant to M. incognita and M. arenaria (McKenry and Anwar, 2006). Somavilla et al (2012) also reported that SO4, Salt Creek, and K 5BB are resistant to M. incognita. Moura et al (2014) reported that MGT 101-14 and K 5BB are resistant to M. incognita.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations